بەرنامەیەکی فێرکاری بۆ خوێندکارانی بەشی پەروەردەی هونەری لە بابەتی دیواربەندی سیرامیکدا (توێژینەوەی هەڵێنجراو) - حسین, جواد نعمت; عبداللە, نعیمة محمد; نادر, فەرەیدون عومەر (Sulaimani Journal for Humanities, 2023)
This research entitled “An Instructional Program for Students of the Department of Art Education on the subject of ceramic murals”, has used the descriptive method, and consists of four chapters. The first part of the research is to introduce the research, which consists of the research problem, the importance of the research, and the aim of the research is to establish an Instructional program for the skills of department of art education students in the subject of ceramic- murals subject at the College of Basic Education at the University of Sulaimani, as well as the scope of the research and the definitions of terms. The second part is the theoretical framework of the research, contains of two main sections. The first section consists of several themes associated with the (Instructional program). The second section also consists of a number of subjects about the (ceramic mural). The third part of the research is the procedures for implementing the research, which includes the method of research, the sample of the research, the tools of the research, and the research community, the program's steps been shown based on the design of )Gerlach & Ely(. In addition to presenting the final evaluation form presented to the program after the program's sections were presented to a group of experts through a survey after solving data with the Cooper equations, as well as presenting the statistical tools used in the research. Section four includes the results of the study, as well as the conclusions of the evaluation, conducted to determine the appropriateness of the program. Finally, recommendations and resources are presented.